Study of solvothermal synthesis of magnesium-based metal-organic frameworks - Abd Aziz, Umar; Mohamed Tahir, Mohamed Ibrahim; Ahmad Aljafree, Nurul Farhana; Abdul Rahman, Mohd Basyaruddin (Malaysian Analytical Sciences Society, 2023)
Metal-organic frameworks (MOFs) are a class of reticular materials consisting of metal ions coordinated to organic ligands. Theoretically, magnesium metal of the s-block has low electronegativity due to their large ionic radii and low ionic charges. The coordination number of magnesium immensely varies depending on the electrostatic interactions with the ligands. Therefore, designing strategic synthesis of Mg-based MOFs becomes a challenge hence its scarcity in literature. This study aims to investigate the different procedure of synthesizing Mg-MOFs using both flexible and rigid organic linkers in organic solvents at high temperature; termed solvothermal method. Magnesium nitrate hexahydrate (Mg(NO3)2.6H2O) are used as the metal source and mixed with naturally occurring plant acids as the organic linkers; malic acid and tartaric acid. Rigidity was introduced by addition of aromatic organic ligands of benzene-1,4-dicarboxylic acid (BDC) and benzene-1,3,5-tricarboxylic acid (BTC). By varying precursor ratios and organic solvents, we hope to improve the reaction condition for the previously reported synthesis of MgMOFs. Single crystal X-ray diffraction (SCXRD) and powder X-ray diffraction (PXRD) analysis showed that the same quality crystals and high crystallinity powder have been produced under improved reaction conditions. The coordination of s-block metal ions has also been found to be most suited in a solvent mixture of H2O and N,N-dimethylformamide (DMF).